2014
DOI: 10.1117/1.jbo.19.4.046013
|View full text |Cite
|
Sign up to set email alerts
|

Full anterior segment biometry with extended imaging range spectral domain optical coherence tomography at 1340 nm

Abstract: We demonstrate an extended-imaging-range anterior-segment optical coherence tomography (eAS-OCT) system for the biometric assessment of full AS in human eye. This newly developed eAS-OCT operating at 1340-nm wavelength band is simultaneously capable of an imaging speed of 120 kHz A-line scan rate, an axial resolution of 7.2 μm, and an extended imaging range of up to 16 mm in air. Imaging results from three healthy subjects and one subject with a narrow-angle demonstrate the instrument's utility. With this syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 59 publications
(102 reference statements)
1
20
0
Order By: Relevance
“…OCT is, in fact, currently being explored to investigate the AOS in animal 15,16 and human eyes. [17][18][19][20][21][22][23][24][25] Several OCT studies have shown the correlation between cross-sectional SC area and IOP, consistent with previous findings of pressure-dependent movement in ex vivo human and nonhuman primate (NHP) eyes using a morphometric analysis system. 26 For example, the SC area has been shown to decrease in response to acute change in IOP in healthy human subjects.…”
Section: Introductionsupporting
confidence: 67%
“…OCT is, in fact, currently being explored to investigate the AOS in animal 15,16 and human eyes. [17][18][19][20][21][22][23][24][25] Several OCT studies have shown the correlation between cross-sectional SC area and IOP, consistent with previous findings of pressure-dependent movement in ex vivo human and nonhuman primate (NHP) eyes using a morphometric analysis system. 26 For example, the SC area has been shown to decrease in response to acute change in IOP in healthy human subjects.…”
Section: Introductionsupporting
confidence: 67%
“…Such an approach has enabled discovery of previously overlooked valve-like elements in human eyes. 38,39 …”
Section: Discussionmentioning
confidence: 99%
“…Automated segmentation algorithms are under development (Dastiridou, A et al IOVS 2016; ARVO Abstract 5119-C0134). In particular, phase-based OCT has shown dynamic motion in TM and post-TM outflow pathways with demonstration of a pulsatile tempo likely related to the cardiac cycle 1317 .…”
Section: Introductionmentioning
confidence: 99%